Linking stem growth respiration to the seasonal course of stem growth and GPP of Scots pine. (16th May 2018) - Chan, Tommy; Berninger, Frank; Kolari, Pasi; Nikinmaa, Eero; Hölttä, Teemu
Abstract: Current methods to study relations between stem respiration and stem growth have been hampered by problems in quantifying stem growth from dendrometer measurements, particularly on a daily time scale. This is mainly due to the water-related influences within these measurements that mask growth. A previously published model was used to remove water-related influences from measured radial stem variations to reveal a daily radial growth signal ( Δ ˆ G m ) . We analysed the intra- and inter-annual relations between Δ ˆ G m and estimated growth respiration rates ( R g ) on a daily scale for 5 years. Results showed that R g was weakly correlated to stem growth prior to tracheid formation, but was significant during the early summer. In the late summer, the correlation decreased slightly relative to the early summer. A 1-day time lag was found of Δ ˆ G m preceding R g . Using wavelet analysis and measurements from eddy covariance, it was found that R g followed gross primary production and temperature with a 2 and 3 h time lag, respectively.This study shows that further in-depth analysis of in-situ growth and growth respiration dynamics is greatly needed, with a focus on cellular respiration at specific developmental stages, its woody tissue costs and linkages to source–sink processes and environmental drivers.